Medication Adherence and Glycemic Control in Older Adults with Type 2 Diabetes: A Cross-Sectional Study in a Community Setting - Tânia Nascimento; Amanda Andrade; Ezequiel Pinto; Catarina Cabrita; Sandra Pais; Rocío de la Puerta (Diabetology)
Background/Objectives: Glycemic control is essential for preventing both short- and long-term complications of type 2 diabetes (T2D), requiring strict adherence to pharmacological therapy. Medication adherence directly influences therapeutic effectiveness, making its assessment in clinical practice crucial. This study aimed to evaluate medication adherence in elderly patients with T2D and its association with glycemic control. Methods: A descriptive cross-sectional study was conducted in the Algarve, Portugal, involving 133 elderly patients (≥60 years) with T2D. Cardiometabolic parameters and medication adherence (global, intentional, and unintentional) were assessed. Statistical analyses were performed using IBM SPSS Statistics 28.0. Results: The study population had a mean age of 71.7 ± 5.7 years, with a predominance of male participants (57.9%) and a high prevalence of dyslipidemia and/or hypertension. Cardiometabolic control was generally poor, with only 26.3% achieving blood pressure targets (≤140/90 mmHg), 8.5% maintaining fasting glycemia within the recommended range (70–110 mg/dL), and 13.6% attaining glycated hemoglobin (HbA1c) values ≤ 7%. Despite this, medication adherence was notably high (97.7%), with no significant association with cardiometabolic control (p > 0.05). Unintentional non-adherence behaviors, such as forgetfulness and inconsistent medication schedules, were the most frequently reported. Conclusions: Although elderly patients with T2D demonstrated high medication adherence rates, their cardiometabolic control remained suboptimal. Unintentional non-adherence behaviors may contribute to poor glycemic control. However, medication adherence alone does not fully explain these outcomes, highlighting the need to assess adherence to other self-care behaviors, particularly dietary and physical activity patterns. Future interventions should integrate comprehensive lifestyle modifications alongside pharmacological management to enhance overall disease control.